Epidemiological study of Kabuto Mountain virus, a novel uukuvirus, in Japan - MENDOZA, Milagros V.; SAWABE, Kyoko; TAKANO, Ai; HAYASAKA, Daisuke; KURODA, Yudai; TATEMOTO, Kango; MUTO, Masahiko; MIZUNO, Junko; YONEMITSU, Kenzo; ISAWA, Haruhiko; MAEDA, Ken; ISHIJIMA, Keita; et al. (Journal of Veterinary Medical Science, 2022)
Kabuto Mountain virus (KAMV), the new member of the genus Uukuvirus, was isolated from the tick Haemaphysalis flava in 2018 in Japan. To date, there is no information on KAMV infection in human and animals. Therefore, serological surveillance of the infection among humans and wild mammals was conducted by virus-neutralization (VN) test and indirect immunofluorescence assay (IFA). Sera of 24 humans, 59 monkeys, 171 wild boars, 233 Sika deer, 7 bears, and 27 nutria in Yamaguchi Prefecture were analyzed by VN test. The positive ratio of humans, monkeys, wild boars, and Sika deer were 20.8%, 3.4%, 33.9% and 4.7%, respectively. No positive samples were detected in bears and nutria. The correlation coefficients between VN test and IFA in human, monkey, wild boar, and Sika deer sera were 0.5745, 0.7198, 0.9967 and 0.9525, respectively. In addition, KAMV was detected in one pool of Haemaphysalis formosensis ticks in Wakayama Prefecture. These results indicated that KAMV or KAMV-like virus is circulating among many wildlife and ticks, and that this virus incidentally infects humans.